Antioxidant defense system in familial hypercholesterolemia and the effects of lipoprotein apheresis. (November 2017) - Blaha, V.; Blaha, M.; Solichová, D.; Krčmová, L. Kujovská; Lánská, M.; Havel, E.; Vyroubal, P.; Zadák, Z.; Žák, P.; Sobotka, L.
Abstract: Oxidative stress is thought to play an important role in the pathogenesis of disorders associated with atherosclerosis. Alpha-tocopherol is considered to be an effective lipophilic antioxidant, which protects lipid membranes against peroxidation and thus prevents cell damage by reaction with free radicals. However, measurement of alpha-tocopherol concentration in serum does not reflect the content of α-tocopherol in membranes whereas erythrocyte alpha-tocopherol may be good indicator of antioxidative status. Therefore a simple isocratic reversed phase HPLC method has been developed and validated for the determination of alpha-tocopherol in human erythrocytes in a clinical setting. The content of alpha-tocopherol in human erythrocyte membrane and lipoperoxidation were studied in patients with severe hypercholesterolemia treated by lipoprotein apheresis. The group of hypercholesterolemic patients (n = 14) treated by lipoprotein apheresis was compared to healthy adult normolipidemic controls. After lipoprotein apheresis, the content of in membrane alpha-tocopherol did not change significantly despite decreased tocopherol in serum and lipoprotein fractions. We observed significantly decreased lipoperoxidation as revealed by serum TBARS, representing end products of lipid peroxidation, which increased from third day afterwards and remained significantly higher in comparison to controls until the next LDL-apheresis. We conclude that aggressive lipid lowering procedure with lipoprotein apheresis was associated with favorable transient decrease of lipoperoxidation. Simultaneously the cell membrane bound antioxidative defense mechanisms as reflected by the content of alpha-tocopherol in human erythrocyte membrane where not depressed in spite of its decreased plasma lipid carrier. Another variables involved remain to be investigated.